Severity of expert-identified behavioural responses of humpback whale, minke whale, and northern bottlenose whale to naval sonar - Sivle, Lise D.; Kvadsheim, Petter H.; Cure, Charlotte; Isojunno, Saana; Wensveen, Paulus Jacobus; Lam, Frans-Peter A.; Visser, Fleur; Kleivane, Lars; Tyack, Peter Lloyd; Harris, Catriona M; Miller, Patrick (Aquatic Mammals, 2015)
Controlled exposure experiments using 1-2kHz sonar signals were conducted with 11 humpback whales, one minke whale and one bottlenose whale during 3 field trials from 2011-2013. Ship approaches without sonar transmissions, playbacks of killer whale vocalizations and broadband noise were conducted as controls. Behavioural parameters such as horizontal movement, diving, social interactions, and vocalizations were recorded by animal-attached tags and by visual and acoustic tracking. Based on these data, two expert panels independently scored the severity of behavioural changes that were judged likely to be responses to the experimental stimuli, using a severity scale ranging from no effect (0) to high potential to affect vital rates (9) if exposed repeatedly. After scoring, consensus was reached with a third-party moderator. In humpback whales, k iller whale playbacks induced more severe responses than sonar exposure, and both sonar exposures and killer whale playbacks induced more responses and responses of higher severity than the no-sonar ship approaches and broadband noise playbacks. The most common response during sonar exposures in all three species was avoidance of the sound source. The most severe responses to sonar (severity 8) were long-term area avoidance by the bottlenose whale and progressive high-speed avoidance in the minke whale. Other severe responses included prolonged avoidance and cessation of feeding (severity 7). The minke whale and bottlenose whale started avoiding the source at a received sound pressure level (SPL) of 146 and 130 dB re 1µPa, respectively. Humpback whales generally had less severe responses that were triggered at higher received levels. The probability of severity scores with potential to affect vital rates increased with increasing SELcum. The single experiments with bottlenose and minke whales suggest they have greater susceptibility to sonar disturbance than humpback whales, but additional studies are needed to confirm this result.